Avaliação do desempenho de técnicas de bioengenharia na proteção e conservação da cobertura final de taludes em aterros de disposição de resíduos sólidos urbanos: estudo de Caso para o Aterro Sanitário de Belo Horizonte,MG - Allan de Freitas Magalhaes (2005)
The aim of this study is to evaluate the performance of bioengineering techniques in conservation and protection of solid waste landfills slopes, contributing to the development of a technology to be used in revegetation of landfill final covers, which can attend the legal and technical criteria. The experiment, implemented in a demonstrative scale, was located at the sanitary landfill of Central de Tratamento de Resíduos Sólidos (CTRS) of BR-040, in Belo Horizonte. The experiment was formed by 33 parcels, representing 10 types of treatments, defined as a combination of two types of fertilization, 4 mixes of species and 2 types of rolled rosion controlled products (RECP), and one control area. The characterization of the area showed a more heterogeneous character in the chemical aspects than on physical aspects of the soil. In the characterization of the vegetation it was verified that phytomass production in the aerial part of the herbaceous was greater than the production on the gramineous species. The most representative species were coloniao and guandu bean. After a period of 12 months, the greater quantities of phytomass by area were reached by the B2M1, B1M1 e CM1 treatments and the lesser ones were obtained by the ASB, B2M3 e CM2 treatments. The highest values of sediment loss were given for the ASB and AP treatments. The treatment using vegetable screen, called biotextil, besides reducing the loss of substrate, presented a good superficial incorporation of organic residuals to the substrate. Nevertheless, its sediment retention efficiency was not higher than the one with reinforced vegetable screen, calledsintemax. The direct relation between the erodibility of rain and loss of soil was confirmed by the observed results. The deleterious effects observed were the attacks of plagues during the initial growing stage of the plants and the spreading of RSU over the vegetation, which made its establishment difficult. The treatments using vegetable screen biotêxtil presented a high cost/benefit relation. For those using the reinforced vegetable screen sintemax, even though of higher cost, the results on soil loss were inferior to those with the other kinds of treatment.